Dialogue on Monarchy in the Gideon-Abimelech Narrative : Ideological Reading in Light of Bakhtin's Dialogism - Lee, Albert Sui-hung (Biblical Interpretation Series, 2021)
"In Dialogue on Monarchy, Albert Sui-hung Lee applies Bakhtin's dialogism to interpret the "unfinalized" dialogue on monarchical ideologies in the Gideon-Abimelech narrative. Lee associates the Bakhtinian concepts of "double-voiced dialogue," "authoring," "unfinalizability," and heteroglossia with the literary features of "twoness," dual images, and macrostructure of the dialogical narrative to illustrate the dialogue of genres as well as that of ideological voices, wherein the pro- and anti-monarchical voices constantly interact with each other. Studying archaeological evidence and literary examinations of prophetic books together, Lee explores the narrative redactor's intention of engaging both remnant and deportee communities in an unfinalized dialogue of different forms of polity for the restoration of their unity and prosperity in exilic and post-exilic contexts"--